Social Capital Influences on Lifelong Learning Among Adults Who Didn’t Finish High School - Clare Strawn (Adult Education Research Conference, 2002)
This paper uses data from the Longitudinal Study of Adult Learning to investigate how discursive and structural dimensions of social capital influence engagement in learning. The primary finding is that social capital influences formal and informal learning in opposite directions.